“The Beach Recovery System” Sebagai Sebuah Konsep Penataan Kawasan Pantai Di Bali Berlandaskan Ajaran Tri Hita Karana - I Nyoman Winia; I Made Adi Widnyana (Jurnal Penelitian Agama Hindu, 2022)
Efforts to save and prevent coastal tourism areas from the threat of abrasion and the threat of monopoly on the use of areas by certain parties need to be pursued, so that the existence of coastal areas that are used as tourist destinations can provide comfort for the user community. As an area that respects local wisdom inherited from its ancestors, Bali always implements policies that are in line with its local wisdom, one of which is the teachings of Tri Hita Karana. In an effort to save and develop a beautiful and comfortable coastal tourism area, it is necessary to design a development system that is in harmony with local wisdom in Bali. The purpose of this paper is to show that The Beach Recovery System is in line with the teachings of Tri Hita Karana and becomes a relevant role model to be applied for the recovery and arrangement of safe and exotic coastal tourism areas. From the study conducted, a strategy for developing a coastal tourism area called The Beach Recovery System was drawn up which is in line with the teachings of Tri Hita Karana owned by the Balinese people. The Beach Recovery System emphasizes the need to determine the supporting components in coastal tourism areas which include: crab, groint, walk way, buffer zone, and green zone. With the fulfillment of these components, surely the welfare expected by the teachings of Tri Hita Karana can be realized in a beautiful and comfortable beach tourism area, which of course will be an attraction for tourists.